Single-sided laser beam welding of a dissimilar AA2024–AA7050 T-joint. (5th July 2015) - Enz, J.; Khomenko, V.; Riekehr, S.; Ventzke, V.; Huber, N.; Kashaev, N.
Graphical abstract: Highlights: Single-sided laser beam welding of a dissimilar AA2024–AA7050 T-joint was realised. For this purpose a fibre laser with high power and a large beam diameter was used. Porosity-free weld seams with low penetration into the skin material were achieved. The mechanical properties are comparable to that of double-sided welded T-joints. Abstract: In the aircraft industry double-sided laser beam welding of skin–stringer joints is an approved method for producing defect-free welds. But due to limited accessibility – as for the welding of skin–clip joints – the applicability of this method is limited. Therefore single-sided laser beam welding of T-joints becomes necessary. This also implies a reduction of the manufacturing effort. However, the main obstacle for the use of single-sided welding of T-joints is the occurrence of weld defects. An additional complexity represents the combination of dissimilar and hard-to-weld aluminium alloys – like Al–Cu and Al–Zn alloys. These alloys offer a high strength-to-density ratio, but are also associated with distinct weldability problems especially for fusion welding techniques like laser beam welding. The present study demonstrates how to overcome the weldability problems during single-sided laser beam welding of a dissimilar T-joint made of AA2024 and AA7050. For this purpose a high-power fibre laser with a large beam diameter is used. Important welding parameters are identified and adjusted for achieving defect-free welds. The obtained joints are compared to double-sided welded joints made of typical aircraft aluminium alloys. In this regard single-sided welded joints showed the expected differing weld seam appearance, but comparable mechanical properties.